Characteristics of Substorm‐Onset‐Related and Nonsubstorm Earthward Fast Flows and Associated Magnetic Flux Transport: THEMIS Observations. Issue 3 (8th March 2021) - Li, Jinxing; Chu, Xiangning; Bortnik, Jacob; Weygand, James; Wang, Chih‐Ping; Liu, Jiang; McPherron, Robert; Kellerman, Adam
Abstract: Substorms are closely associated with fast flows; however, many fast flows are not associated with substorm onsets and only lead to a localized, transient, and weak response in the magnetosphere and ionosphere. This study uses the midlatitude positive bay index to identify substorms. A case study investigates the magnetospheric and ionospheric responses to substorm‐onset‐related fast flows and nonsubstorm fast flows using observations from the THEMIS spacecraft and ionospheric currents. Statistics based on THEMIS observations made over 11 years show that substorm‐onset‐related fast flows are more likely to penetrate closer to the Earth and spread over a wider range of MLTs compared to nonsubstorm fast flows. The substorm‐onset‐related fast flow durations are slightly longer than nonsubstorm fast flow on average, and there is no significant difference between their peak velocity probability distributions. However, substorm‐onset‐related fast flows are statistically shown to be accompanied by substantially larger B z increases that persist for longer periods of time, and hence result in 80% larger earthward‐directed magnetic flux transport rates. Plain Language Summary: A substorm is a series of magnetic disturbances in the Earth's magnetized space known as the magnetosphere. It is associated with earthward‐directed fast flows that bring magnetic energy into the inner magnetosphere. However, not every single fast flow is associated with a substorm. This study statistically investigated the substorm‐onset‐related fast flows and nonsubstorm fast flows using THEMIS spacecraft measurements from 2008 to 2018. Our conclusions are as follows. (1) Substorm‐onset‐related fast flows have a larger probability of penetrating closer to the Earth and spreading over a wider MLT range than nonsubstorm fast flows. (2) The flow velocity and flow duration are not key factors that lead to the differences between substorm and nonsubstorm fast flows. (3) Substorm‐onset‐related fast flows are typically accompanied by a larger magnetic field increase and a larger magnetic field energy input than nonsubstorm fast flows. (4) Case studies show that substorm‐onset‐related fast flows are associated with vortices that form in the resulting ionospheric currents. Key Points: Substorm‐onset‐related fast flows are accompanied by stronger Bz increases and larger magnetic flux transport than nonsubstorm fast flows Substorm‐onset‐related fast flows have a higher probability of penetrating to geosynchronous orbit compared to nonsubstorm fast flows Substorm‐onset‐related fast flows statistically last 21% longer than nonsubstorm fast flows, and velocities do not differ between the two